Parents’ relationship to pain during children’s cancer treatment – a preliminary validation of the Pain Flexibility Scale for Parents - Thorsell Cederberg, Jenny (J Pain Res, 2017)
OBJECTIVES: Pain is one of the most frequent and burdensome symptoms for children with cancer. Psychological acceptance has been shown to be beneficial in chronic pain. Acceptance-based interventions for experimentally induced pain have been shown to predict increased pain tolerance and decreased pain intensity. An acceptance-based pilot study for children with cancer experiencing pain has shown promising results. Further, parental acceptance has been shown to predict decreased child distress. To date, no instruments measuring acceptance in the context of acute pain in children are available. The aim of this study was to develop and evaluate an instrument to measure acceptance in parents of children experiencing pain during cancer treatment. METHODS: A test version of the Pain Flexibility Scale for Parents (PFS-P) was sent to parents of all children undergoing cancer treatment in Sweden at the time of the study. Exploratory factor analysis (n=243) examined numerous solutions. Internal consistency, test–retest reliability and convergent validity were calculated. RESULTS: A three-factor Promax solution best represented the data. The subscales were pain resistance, valued action and pain fusion. Internal consistency was good (α=0.81–0.93), and the total scale and the subscales demonstrated temporal stability (r=0.76–0.87) and good convergent validity (−0.40 to −0.84). DISCUSSION: The PFS-P measuring acceptance in parents of children experiencing pain during cancer treatment is now available, enabling evaluation of acceptance in the context of acute pain in children. The scale shows good psychometric properties but needs further validation.